Pengaruh Ketersediaan Alat Medis dan Kompetensi Tenaga Kesehatan terhadap Kualitas Pelayanan Kesehatan dengan Peran Mediasi Manajemen Mutu Rumah Sakit - Elyza Nurulita Syari; Adya Hermawati; M. N. Lisan Sediawan; Muryati Muryati; Aji Suraji (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Healthcare service quality is an important indicator of hospital performance and is influenced by the availability of medical equipment, healthcare worker competency, and effective hospital quality management. This study aimed to analyze the effects of medical equipment availability and healthcare worker competency on healthcare service quality, with hospital quality management as a mediating variable, among inpatients at a Type C hospital in Bulungan Regency, North Kalimantan. This research employed a quantitative explanatory approach with a causal associative design. Data were collected from hospitalized patients using structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicated that medical equipment availability, healthcare worker competency, and hospital quality management had significant positive effects on healthcare service quality. In addition, medical equipment availability and healthcare worker competency significantly influenced hospital quality management, which also served as a significant mediating variable in improving healthcare service quality. These findings suggest that enhancing healthcare service quality requires an integrated strategy involving adequate medical equipment, competent healthcare professionals, and a well-implemented hospital quality management system. Strengthening these aspects is expected to improve service performance and patient satisfaction, particularly in Type C hospitals.